PREPARATION OF BACHELORS OF PEDAGOGICAL EDUCATION FOR THE FORMATION OF CIVIL IDENTITY OF CHILDREN AND ADOLESCENTS DURING SUMMER PEDAGOGICAL PRACTICE - L. Saenko; E. Zritneva; T. Zateeva (Вестник Северо-Кавказского федерального университета)
The concepts of «identity», «civic identity», and «formation of identity» are considered in the article. The relationship between civic identity and the general culture of the individual is highlighted. It is noted that the formation of civic identity is a targeted process of the formation of a civic culture of the individual. The structure of civic identity is defined, its components are identified (cognitive, value-semantic, emotional, activity). The authors give their own interpretation of the concept of «civic identity». The structure and periods of the camp shift are presented and the basic measures for the formation of the civic identity of children and adolescents for each period are determined. The pedagogical features of the stay of children and adolescents in the summer recreation camp are determined. The signs of the functioning of the children's recreation camp are highlighted.